The Effect Of Kopi Kenangan Online Menus On Consumers’ Purchase Intention During The Covid-19 Pandemic - Dinda Saphira Nabila Sofyan; Arif Hartono (Eduvest - Journal of Universal Studies, 2022)
This study examined consumers purchase intentions during the pandemic in relation to the online food menu under the extended S-O-R framework, particularly with Kopi Kenangan as the object. Kopi Kenangan is one of fastest-growing grab-andgo coffee chains in Indonesia. The purpose of this study is to discover the factors driving people intention to purchase Kopi Kenangan products through online food ordering platforms. In the data collection process, 250 samples from Kopi Kenangan consumers who had previously purchased them online were used, which involved distributing online questionnaires using Google forms. The data was then further analyzed using the PLS-SEM approach. The result shows that menu visual appeal and menu informativeness positively affected desire for food. The perception of COVID-19 risks positively affected the perceived convenience of online food ordering as well. While, desire for food and perceived convenience also positively affected purchase intention